Effects of BoGHV-4 and LPS on key inflammatory molecules: insights from primary culture studies - Romeo, Florencia (2025)
Bovine gammaherpesvirus 4 (BoGHV-4) has been frequently associated with postpartum uterine infections in cattle; however, its pathogenesis and interaction with bacterial components remain poorly understood. This study investigated the effects of BoGHV-4 infection and Escherichia coli lipopolysaccharide (LPS) on Toll-like receptor 4 (TLR4) activation and downstream immune modulation in primary bovine endometrial cells (BECs). The expression and secretion of TLR4, CXCL8, interferon-γ (IFN-γ), and tumour necrosis factor) were evaluated over time. LPS markedly upregulated TLR4 expression, whereas BoGHV-4 alone led to late-stage downregulation. Co-stimulation with BoGHV-4 and LPS initially enhanced TLR4 expression but resulted in suppression at later time points. CXCL8 and IFN-γ levels increased significantly, particularly under BoGHV- 4 +LPS conditions, suggesting synergistic amplification of inflammatory signalling. Conversely, TNFα (TNFα remained undetectable, implying tight post-transcriptional control. These findings highlight the intricate virus–bacterium interplay in the bovine endometrium and provide mechanistic insight into BoGHV-4-associated uterine pathology